A characterization of the dynamical ascending routing - Bouabdallah, A.; Trehel, M. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
A characterization of a routing defined on a dynamical logical structure is presented. By uniting the structure with the messages destabilizing it, an invariant is obtained, that allows a simple proof of the properties of the routing. The results are exploited by designing and structuring the proof of the mutual exclusion algorithm, which uses this routing. The specifications are done in an axiomatic manner, and the proof is given in a temporal framework.< >